So sánh \(R=\frac{x^2+x+1}{x}\)với 3
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
ĐKXĐ: \(\hept{\begin{cases}x\ne1\\x^2+x+1\ne0\end{cases}}\)
a/ \(R=1:\left[\frac{x^2+2}{\left(x-1\right)\left(x^2+x+1\right)}+\frac{x+1}{x^2+x+1}-\frac{1}{x-1}\right]\)
\(=1:\left[\frac{x^2+2+\left(x+1\right)\left(x-1\right)-\left(x^2+x+1\right)}{\left(x-1\right)\left(x^2+x+1\right)}\right]=1:\left(\frac{x^2+2+x^2-1-x^2-x-1}{\left(x-1\right)\left(x^2+x+1\right)}\right)\)
\(=1:\left[\frac{x^2-x}{\left(x-1\right)\left(x^2+x+1\right)}\right]=1:\left[\frac{x\left(x-1\right)}{\left(x-1\right)\left(x^2+x+1\right)}\right]=1:\left(\frac{x}{x^2+x+1}\right)\)
\(=\frac{x^2+x+1}{x}\)
b/ Ta có: \(R=\frac{x^2+x+1}{x}=3+\frac{\left(x-1\right)^2}{x}>3\)
Vậy R > 3
a: R-3=(x^2+x-1-3x)/x=(x-1)^2/x
Nếu x>0 thì R-3>0
=>R>3
Nếu x<0 thì R-3<0
=>R<3
c: Để R>4 thì R-4>0
=>\(\dfrac{x^2+x+1-4x}{x}>0\)
=>\(\dfrac{x^2-3x+1}{x}>0\)
TH1: x>0 và x^2-3x+1>0
=>x>0 và \(\left[{}\begin{matrix}x< \dfrac{3-\sqrt{5}}{2}\\x>\dfrac{3+\sqrt{5}}{2}\end{matrix}\right.\Leftrightarrow x>\dfrac{3+\sqrt{5}}{2}\)
mà x nguyên
nên x>3
TH2: x<0 và x^2-3x+1<0
=>x<0 và \(\dfrac{3-\sqrt{5}}{2}< x< \dfrac{3+\sqrt{5}}{2}\)(loại)
a) \(ĐKXĐ:\) \(x\ne1,x>0\)
\(P=1:\left(\frac{x+2}{x\sqrt{x}-1}+\frac{\sqrt{x}+1}{x+\sqrt{x}+1}-\frac{\sqrt{x}+1}{x-1}\right)\)
\(=1:\left(\frac{x+2}{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}+\frac{\left(\sqrt{x}+1\right)\left(\sqrt{x}-1\right)}{\left(\sqrt{x}+1\right)\left(x-\sqrt{x}+1\right)}-\frac{x+\sqrt{x}+1}{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}\right)\)
\(=1:\left[\frac{x+2+x-1-\left(x+\sqrt{x}+1\right)}{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}\right]\)
\(=1:\frac{\sqrt{x}.\left(\sqrt{x}-1\right)}{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}=\frac{x+\sqrt{x}+1}{\sqrt{x}}\)
Vậy \(P=\frac{x+\sqrt{x}+1}{\sqrt{x}}\left(x\ne1,x>0\right)\)
b) Xét hiệu \(P-3=\frac{x+\sqrt{x}+1}{\sqrt{x}}-3\)
\(=\frac{x+\sqrt{x}+1-3\sqrt{x}}{\sqrt{x}}=\frac{\left(\sqrt{x}-1\right)^2}{\sqrt{x}}>0\) \(\forall x>0,x\ne1\)
Do đó : \(P>3\)
a: \(P=\dfrac{4x-6-x+1}{2x-3}:\left(\dfrac{6x+1}{2x^2-3x+2x-3}+\dfrac{x}{x+1}\right)\)
\(=\dfrac{3x-5}{2x-3}:\left(\dfrac{6x+1}{\left(x+1\right)\left(2x-3\right)}+\dfrac{x}{x+1}\right)\)
\(=\dfrac{3x-5}{2x-3}:\dfrac{6x+1+2x^2-3x}{\left(x+1\right)\left(2x-3\right)}\)
\(=\dfrac{3x-5}{\left(2x-3\right)}\cdot\dfrac{\left(2x-3\right)\left(x+1\right)}{2x^2+3x+1}\)
\(=\dfrac{3x-5}{2x+1}\)
b: \(P-\dfrac{3}{2}=\dfrac{3x-5}{2x+1}-\dfrac{3}{2}=\dfrac{6x-10-6x-3}{2\left(2x+1\right)}=\dfrac{-7}{2\left(2x+1\right)}\)
\(R=\frac{x^2+x+1}{x}=\frac{3x+x^2-2x+1}{x}=\frac{3x+\left(x-1\right)^2}{x}=3+\frac{\left(x-1\right)^2}{x}\ge3\)
\(R=\frac{x^2+x+1}{x}=\frac{3x+x^2-2x+1}{x}=\frac{3x+\left(x-1\right)^2}{x}=3+\frac{\left(x-1\right)^2}{x}\ge3\)